The Relationship Between Sense of Competence and Parental Involvement in Caring for Children with Special Needs - Herlina Herlina; Ismawati Kosasih; Helli Ihsan; Lira Fessia Damaianti; MIF Baihaqi (Research Synergy Foundation, 2025)
This research was conducted to determine the relationship between competent parental involvement in caring for, handling, and educating children with birth impairment children. It involved 185 Bandung-based parents of children with a birth impairment. Skala Evaluasi Diri Kompetensi-Anak Berkebutuhan Khusus or SEDKO-ABK (Self-Evaluation Competence Scale for Parents with Children with Special Needs) was used as the instrument to measure the sense of competence, while parental involvement was measured using Kuesioner Keterlibatan Orang Tua dalam Pengasuhan Anak or KUKOPA (Questionnaire on Parental Involvement in Caring for Children). The results show that parental involvement in caring for, handling, and educating children with special needs. Based on the results of this research, training for parents is important to their understanding and skills in caring for children with a birth impairment.